The relationship between reading anxiety and academic reading performance among ESL learners - Mohd. Zin, Zuhana (2007)
The purpose of this study is to examine the possible relationship between reading anxiety among university ESL learners and their performance in comprehending academic texts. This study was conducted based on the assumption that anxiety could be another factor which could explain the differences in comprehension performance among the ESL learners. The subjects who participated in this study were the low proficiency Malay ESL learners from Kolej Sains dan Teknologi, Universiti Teknologi Malaysia, Kuala Lumpur who had just entered the university. This study adopted correlation design which employed quantitative approaches. Two survey questionnaires, namely Foreign Language Reading Anxiety Scales (FLRAS) and Cognitive Interference Questionnaire (CIQ) were utilized to measure the level of reading anxiety and the interference in the subjects cognitive systems of the subjects. Their comprehension performance were measured by means of a reading comprehension test and a written recall task. The results gained from this study indicated that the subjects’ comprehension performance were inversely related to reading anxiety which suggests reading anxiety plays a role in influencing the low proficiency ESL learners when reading academic texts. In addition, the findings also demonstrated that the interference experienced by the subjects while engaging in the reading tasks was related to the level of anxiety reactions. However, the findings can only be generalized to the samples involved in this study. Further studies to investigate the influence of reading anxiety should include other ESL learners from other local universities to enable the results to be generalized to general population.